Evaluation of Farmers Saved Seed of Green Gram and Chickpea in Munger District of Bihar - Kumar, Mukesh; Kumar, Amarendra; Kumar, Rakesh; Kumari, Hemlata (International Journal of Bio-resource and Stress Management, 2023)
An investigation was conducted in 60 rural households of 8 villages viz, Pouria, Durgapur, Sangrampur, Jala, Supoor Jamua, Kendua, Khapra and Jhikli located within a range of 10 km to assess the seed quality of farmers saved seed of green gram and chickpea, in Munger district of Bihar during 2014−15. The seed sample were collected from the farmers saved seed stored under different container for estimation of seed quality attributes such as seed moisture content, physical purity, germination percent and seed health. It was found that seed storage as well as the quantity of the storage decided the type of the container and their storage methods. The commonly used methods and containers are Polythene bag, Metal container and Jute bag. The polythene bag were found most common storage container for green gram where as for chickpea more than 50% farmers prefers metal container. It was found that only 23.33% farmer treated the green gram whereas number was more in case of chickpea (53.33%) for storage. The germination percent of twenty out of thirty sample of green gram and all fifteen samples of chickpea maintained the prescribed IMSCS standard. The storage of farmer saved seed of both crops was not satisfactory with regard to seed moisture content and insect pest infestation. The current evidence on farmer’s seed samples indicated that storage methods and seed quality parameters need to be improved to increase yield.